Mothers' autonomy and childhood stunting: evidence from semi-urban communities in Lao PDR - Yusuke Kamiya; Marika Nomura; Hina Ogino; Kanako Yoshikawa; Latsamy Siengsounthone; Phonepadith Xangsayarath (BMC, 2018)
Abstract Background Childhood stunting (height-for-age z-scores below − 2), a form of chronic undernutrition, remains a global health burden. Although a growing literature has examined the association between mothers' autonomy and childhood stunting, these studies have been limited to countries in South Asia or Sub-Saharan Africa where women have relatively lower social status than do men. Little research has analyzed the effect of mothers' autonomy on childhood stunting in Lao PDR, where women's social status is relatively high compared to that in other countries. Methods We conducted a cross-sectional questionnaire and body scale measurement targeting 100 mothers and their 115 children (<5 years old) from semi-urban communities in Lao PDR, which is the country with the highest prevalence of childhood stunting in the Indochina region. As dimensions of women's autonomy, we measured self-esteem, self-efficacy, decision-making power, freedom of mobility, and control of money. We then analyzed how each dimension was associated with the likelihood of childhood stunting. Results The likelihood of childhood stunting was significantly lower if mothers had higher self-efficacy for health care (OR = 0.15, p = 0.007), self-esteem (OR = 0.11, p = 0.025), or control of money (OR = 0.11, p = 0.041). In contrast, mothers' decision-making power and freedom of mobility were not significantly associated with childhood stunting. Conclusions We clarified which dimensions of women's autonomy were associated with childhood stunting in Lao PDR. A closer examination of mothers' autonomy will aid proper understanding of the determinants of childhood stunting.